2022
DOI: 10.1186/s12967-022-03493-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes in the pathogenesis, diagnosis, and treatment of central nervous system diseases

Abstract: Central nervous system (CNS) diseases, such as multiple sclerosis, Alzheimer's disease (AD), and Parkinson’s disease (PD), affect millions of people around the world. Great efforts were put in disease related research, but few breakthroughs have been made in the diagnostic and therapeutic approaches. Exosomes are cell-derived extracellular vesicles containing diverse biologically active molecules secreted by their cell of origin. These contents, including nucleic acids, proteins, lipids, amino acids, and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 156 publications
0
55
0
Order By: Relevance
“…In the last decade, it has become evident to the scientific community that EV cargo can indeed contain molecules such as miRNAs, as we confirmed in the former and present paper, that can be themselves new targets or can target key cellular pathways in the receiving cells, suggesting that they could be considered as a tool for new potential gene therapies. Moreover, EVs can easily cross the blood–brain barrier and can be exploited to deliver drugs [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, it has become evident to the scientific community that EV cargo can indeed contain molecules such as miRNAs, as we confirmed in the former and present paper, that can be themselves new targets or can target key cellular pathways in the receiving cells, suggesting that they could be considered as a tool for new potential gene therapies. Moreover, EVs can easily cross the blood–brain barrier and can be exploited to deliver drugs [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, as an important site of ROS and energy metabolism, may play a key role in the prevention of RILI [ 45 ]. In addition, exosomes are often used as therapeutic drug carriers in clinical applications [ 46 , 47 ], with the rise of nanomaterials and the perfection of the principles of nanoparticle design, nanoantioxidants may be able to exert radiation protection by targeting lung tissue specifically [ 48 , 49 ], which we could combine the purified TLR4-activated macrophage-derived exosomes with nanomaterials for precise treatment of RILI. On the other hand, related studies have shown that statins have significant radioprotective effects, but the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons (Fig. 2 ), various aspects of disease deal with the control of protein misfolding within cargos of EV lumen [ 59 , 60 ]. Biomarkers of these and other vesicles, involved in clinical diseases, include endosomes, endo-lysosomes [ 61 ] and APhs [ 27 ].…”
Section: Role Of Ups In Diseasesmentioning
confidence: 99%
“…In these cases various stages of the diseases involve exosomes, released not only by neuron cell bodies but also by dendrites and axon terminals (Fig. 2 ) [ 57 59 ].
Fig.
…”
Section: Role Of Ups In Diseasesmentioning
confidence: 99%